THE LIFECYCLE THEORY OF COMPETITION LAW SYSTEMS (World Bulletin of Management and Law, 2024)
This article offers an in-depth exploration of the "lifecycle" theory and the evolutionary trajectories of competition systems, particularly those that surfaced in the late 1980s. The foundational theory was proposed by William Evan Kovacic and Marianela Lopez-Galdos following their comprehensive analysis of the institutional design of competition agencies across various developing nations. This examination provided valuable insights into the structural and functional dynamics of these agencies. Additionally, the article will systematically discuss the myriad of factors that either facilitate or impede the effectiveness of competitive systems. Central to this paper is a thorough discussion on the development of robust criteria for assessing the lifecycle of competition systems.